Reliability modeling with applications: essays in honor of Professor Toshio Nakagawa on his 70th birthday - Nakamura, Syouji; Qian, Cun Hua; Chen, Mingchih (World Scientific Publishing Co. Pte. Ltd, 2013)
Reliability modeling has been a major concern for engineers and managers engaged in high quality system designs. This book presents the recent advancement in reliability theory and reliability engineering. Starting from maintenance policies, the book introduces reliability analysis to systems using stochastic processes to study their optimization problems. In this book, the authors will illustrate how these techniques of reliability are applied to solve optimization problems in computer, information and network systems.